Agriculture for nutrition and health - Grace, Delia; McDermott, John J. (International Livestock Research Institute, 2012)
The Consultative Group on International Agricultural Research (CGIAR) was born in the 1960s amidst widespread concern of a Malthusian crisis looming in poor countries. In the last 40 years, the world has managed to feed its growing population (some too much and some too little) thanks to many initiatives and actors, not least international agricultural research. The last 4 decades have also seen concerns about agriculture widen from food quantity to food quality and safety, from farms to the whole value chain, from productivity to environmental impacts, and from profits to poverty and gender equity. This paper describes how, in response to changing demands, the CGIAR transited in 2010 from an informally managed, academically oriented system to a more structured model emphasizing impact, accountability and collaboration. As part of this change, a major new program was launched in 2012 on leveraging agriculture to improve human nutrition and health. Three of the program components focus on nutrition and one component focuses on human disease problems where agriculture contributes to the problem and potentially the solutions. The agriculture and health priorities have been identified as foodborne disease, zoonoses, and emerging diseases. Ecohealth/One Health provides an over-arching framework for this component and we describe the focus, activities, partnership strategy and impact pathway situated in an Ecohealth/One Health conceptual framework. We also cite examples from recently completed projects showing how CGIAR research could have a key role in improving the management of health risks that have their origin on farms and in food chains.